2019
DOI: 10.1155/2019/9695412
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria- and Oxidative Stress-Targeting Substances in Cognitive Decline-Related Disorders: From Molecular Mechanisms to Clinical Evidence

Abstract: Alzheimer’s disease (AD) is the most common form of dementia affecting people mainly in their sixth decade of life and at a higher age. It is an extensively studied neurodegenerative disorder yet incurable to date. While its main postmortem brain hallmarks are the presence of amyloid-βplaques and hyperphosphorylated tau tangles, the onset of the disease seems to be largely correlated to mitochondrial dysfunction, an early event in the disease pathogenesis. AD is characterized by flawed energy metabolism in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 166 publications
(190 reference statements)
1
58
0
1
Order By: Relevance
“…61,70,71,74,[77][78][79][80] Manifestations of OS are hallmark symptoms in neurological disease, including cognitive deficits. 52,54,65,76,79,[81][82][83][84][85][86][87][88] In concert with the above, a correlation was found between OS in the CNS and demyelination, which results in the loss of integrity and proper maintenance of oligodendrocytes and their myelin sheaths, the latter being crucial for cognitive performance and higher brain function. 57,[89][90][91] Thus, inclusion of strategies for enhancing mitochondrial biogenesis, function, and protection 68,80,[92][93][94][95][96] that may also rely on pathways epigenetically induced by diet [97][98][99][100][101][102][103][104][105][106][107][108] and/or exercise 99,100,…”
Section: Introductionmentioning
confidence: 77%
“…61,70,71,74,[77][78][79][80] Manifestations of OS are hallmark symptoms in neurological disease, including cognitive deficits. 52,54,65,76,79,[81][82][83][84][85][86][87][88] In concert with the above, a correlation was found between OS in the CNS and demyelination, which results in the loss of integrity and proper maintenance of oligodendrocytes and their myelin sheaths, the latter being crucial for cognitive performance and higher brain function. 57,[89][90][91] Thus, inclusion of strategies for enhancing mitochondrial biogenesis, function, and protection 68,80,[92][93][94][95][96] that may also rely on pathways epigenetically induced by diet [97][98][99][100][101][102][103][104][105][106][107][108] and/or exercise 99,100,…”
Section: Introductionmentioning
confidence: 77%
“…This results in a vicious cycle of increased ROS through age-associated mitochondrial dysfunction, which again accelerates the aging process [36]. Polyphenols, due to their potential in ROS-scavenging, have emerged as a potentially powerful strategy to ameliorate oxidative stress and thus induce health and longevity [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial damage has been reported in both AD (Swerdlow, 2018) and depression (Bansal and Kuhad, 2016) and both patient groups show reduced glucose metabolism using fluorodeoxyglucose (FDG) PET (Hunt et al, 2007;Wei et al, 2016;Rice and Bisdas, 2017;Fu et al, 2018). Supporting this, a Ginkgo biloba extract (GBE) that has free radical scavenging properties, enhances mitochondrial membrane potential, and increase ATP production (Lejri et al, 2019) revealed a significant effect on apathy and other NPDs in AD patients (Scripnikov et al, 2007). On the contrary, a recent RCT found no effect on NPDs when patients were treated with resveratrol which acts on several proteins important for mitochondrial function (Zhu et al, 2018).…”
Section: Pharmacologic Interventionsmentioning
confidence: 96%